Aminoacylase efficiently hydrolyses fatty acid amino acid conjugates of Helicoverpa armigera potentially to increase the pool of glutamine - Kallure, Gopal S.; Sahoo, Shubhranshu Shekhar; Kale, Rutuja S.; Barvkar, Vitthal T.; Kontham, Ravindar; Giri, Ashok P. (Insect Biochemistry and Molecular Biology, 2024)
One of the most prevalent bioactive molecules present in the oral secretion (OS) of lepidopteran insects is fatty acid amino acid conjugates (FACs). Insect dietary components have influence on the synthesis and retaining the pool of FACs in the OS. We noted differential and diet-specific accumulation of FACs in the OS of Helicoverpa armigera by using Liquid Chromatography-Quadrupole Time of Flight Mass Spectrometry. Interestingly, we identified FACs hydrolyzing enzyme aminoacylase (HaACY) in the OS of H. armigera through proteomic analysis. Next, we have cloned, expressed, and purified active recombinant HaACY in the bacterial system. Recombinant HaACY hydrolyzes all the six identified FACs in the OS of H. armigera larvae fed on host and non-host plants and releases respective fatty acid and glutamine. In these six FACs, fatty acid moieties vary while amino acid glutamine was common. Glutamine obtained upon hydrolysis of FACs by HaACY might serve as an amino acid pool for insect growth and development. To understand the substrate choices of HaACY, we chemically synthesized, purified, and characterized all the six FACs. Interestingly, rHaACY also shows hydrolysis of synthetic FACs into respective fatty acid and glutamine. Our results underline the importance of diet on accumulation of FACs and role of aminoacylase(s) in regulating the level of FACs and glutamine.
Keywords: Aminoacylase; Fatty acid amino acid conjugates; Glutamine; Helicoverpa armigera; Oral secretion